The Influence of Digital Literacy on Student Learning Outcomes in High School - Ahmad Syauqi Pamungkas; Didit Darmawan; Rahayu Mahardikaningsih (Molang: Journal Islamic Education, 2026)
Digital technology is increasingly being integrated into education, and students must possess digital literacy skills to effectively utilize and access information during the learning process. This study was conducted to study the impact of digital literacy on high school students' learning outcomes through a literature review. This method employs a qualitative approach using a literature review methodology, drawing on various relevant journal articles and scientific publications. An analysis was conducted on ten studies discussing the relationship between digital literacy and student learning outcomes. The findings indicate that digital literacy has a positive effect on learning outcomes because it helps students access a wider range of learning resources and improves their understanding of the learning material. Therefore, strengthening digital literacy is a crucial effort to improve the quality of learning in the era of digital education. Additionally, digital literacy helps students improve their critical thinking, communication, collaboration, creativity, and independent learning skills.